The relationship between student motivation and learning achievements from a sociocultural perspective: A case study of the Police University = mối quan hệ giữa động cơ và kết quả học tập của sinh viên dựa trên quan điểm lý thuyết văn hóa xã hội qua kết q - Lê, Hương Hoa (University of Languages and International Studies, 2017)
155 tr. + CD-ROM+ Tóm tắt